DESAIN SISTEM INFORMASI GEOGRAFIS PARIWISATA KOTA SEMARANG DENGAN GOOGLE API (Information Technology and Telematics, 2015)
Abstract-- Tourism is one of the mainstays of Indonesia to earn income. Proper management became one of the capital to develop the tourism sector as a superior product. With the increasing number of tourist attractions in Semarang, the necessary means to summarize the information from these places. A tour concept means associated with the place or location. Thus it takes a container of information that is capable of displaying a place or location as accurately and as easy as possible to reach them. One solution to be able to show both the information in the right format is a dynamic map in the form of a Geographic Information System (GIS). Geographic Information System (GIS) designed to collect, store and analyze an object where geographical location is an important characteristic, and requires critical analysis. Handling and analysis of data based on geographic location is the key to GIS. so that visitors can easily to find   tourism location in the city of Semarang. Keywords-- WebGis, Google Maps, Tourism, Semarang